A Mechanism to Support Agile Frameworks Enhancing Reliability Assessment for SCS Development: A Case Study of Medical Surgery Departments - Thawaba, A.A. (Springer, 2020)
Safety-critical systems (SCSs) are distributed in many areas such as flight, railway, medical, nuclear and defense, and failure of these systems can harm human life or damage the environment. There are several ways to reduce or possibly eliminate failure, according to researchers improving the development processes of SCSs reduces failure by 40. Therefore, developers have invented many development methods and measurement techniques to reduce failures during development processes. Agile Software Development (ASD) has entered the field of safety-critical system development (SCSD) in the past few years. Agile has produced reliable and high-quality products by expanding its principles and adapting new measurement techniques. However, there is still a gap in improving measurement techniques and stopping failures. This paper proposed a new measurement mechanism called Package Metrics for Improving Software Development (PM-ISD). The proposed measurement enhances reliability assessment and decision-making during agile development processes. PM-ISD assists the Agile management team throughout the Medical Surgery Department (MSD) project phases to track the completion of tasks. Â© Springer Nature Switzerland AG 2020.